ATTENUATED AFRICAN SWINE FEVER VIRUS AND ITS USE AS A VACCINE - BLOT LE POTIER Marie- Frédérique; CHASTAGNER Amélie; BOURRY Olivier; LUCAS Pierrick; HUTET Evelyne; PABOEUF Frédéric; LE DIMNA Mireille; BLANCHARD Yannick (2023)
The present invention relates to an attenuated African Swine Fever (ASF) virus, wherein : â¿¢ genes MGF 360-12L, 360-13L, 360-14L, 505-2R, 505-3R are deleted or are interrupted or mutated such that the genes are not transcribed and/or translated, â¿¢ ORF of ASFV_G_ACD_00520 is deleted or is interrupted or mutated such that it is not transcribed and/or translated, and â¿¢ genes MGF 505-1 R et 505-4R are truncated, compared to the genome of the corresponding unattenuated virus. The present invention also refers to a vaccine comprising the attenuated ASF virus, and its use in preventing African Swine Fever in a subject. The present invention also relates to an in-vitro method for obtaining the attenuated ASF virus, which comprises at least one step of thermal- attenuation of a virulent ASFV virus strain selected among Georgia 2007/1, Pig/HLJ/2018, a strain of ASF virus of genotype II or a genetically close ASF virus strain, and amplification by inoculation of Specific-Pathogen- Free pigs and selecting said attenuated ASF virus. The present invention refers to an in vitro method for the differential detection of the attenuated ASF virus and of the corresponding non- attenuated ASF virus as well. La presente invención se relaciona con un virus atenuado de la peste porcina africana (PPA), en donde: los genes MGF 360-12L, 360-13L, 360-14L, 505-2R, 505-3R se eliminan o se interrumpen o mutan de tal manera que los genes no se transcriben y/o se traducen, el ORF del VPPA_G_ACD_00520 se elimina o se interrumpe o muta de tal manera que no se transcribe ni se traduce, y los genes MGF 505-1 R y 505-4R se truncan, en comparación con el genoma del virus no atenuado correspondiente. La presente invención también se refiere a una vacuna que comprende el virus atenuado de la PPA, y su uso en la prevención de la peste porcina africana en un sujeto. La presente invención también se refiere a un método in vitro para obtener el virus atenuado de la PPA, que comprende al menos una etapa de atenuación térmica de una cepa virulenta de virus del VPPA seleccionada entre Georgia 2007/1, Cerdo/HLJ/2018, una cepa del virus de la PPA del genotipo II o una cepa del virus de la PPA genéticamente cerrada, y la amplificación por inoculación de cerdos libres de patógenos específicos y la selección del virus atenuado de la PPA. La presente invención se refiere a un método in vitro para la detección diferencial del virus atenuado de la PPA y también del virus no atenuado de la PPA correspondiente.